Rancang Bangun Sistem E-Catalog Produk Berbasis Web pada PT. Paletindo Prakarsa Unggul - Ardian Setiawan; Farizi Ilham; Muhammad Sunandi Irsyad; Nasrul Aziz Suandi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
PT. Paletindo Prakarsa Unggul faces significant challenge in conveying proudct information, which is unstructured and inefficient due to manual catalog management, resulting in repetitive administrative workload and difficulties for customers in searching for products. Therefore, this study aims to design and develop a web-based product E-Catalog system capable of comprehensively digitizing and cetralizing pallet product data. System development was conducted using the Waterfall method, consisting of the requirements analysis, desing, implementation, and testing phases, adopting Next.js, TypeScript, Supabase, and Tailwind CSS as the primary technology stack. The implementation results demonstrate that the system successfully provides crucial features such as an Administrative Control Panel (CMS) for product data management, product search and filtering features, and a page with complete specification details. Functionallity testing proved that this E-Catalog system is capable of simplifying product data management, accelerating the delivery of information to customers, and improving the efficiency of the company’s promotional processes. Thus, this web-based E-Catalog system has proven effective in presenting PT. Paletindo Prakarsa Unggul’s product information in a more structured and modern manner, while simultaneously resolving efficiency issues in conventional promotional media.